Significance of baseline and change in neutrophil-to-lymphocyte ratio in predicting prognosis: a retrospective analysis in advanced pancreatic ductal adenocarcinoma - Yang Chen (Nature Portfolio, 2017)
Abstract The neutrophil-lymphocyte ratio (NLR) has been reported to be associated with prognosis in several cancers. The objective of our study was to evaluate the prognostic role of baseline NLR and change in NLR (ΔNLR) in advanced pancreatic cancer underwent chemotherapy. Between January 2010 and June 2015, 132 patients underwent chemotherapy were eligible for assessment. Based on our patients’ data, the cut-off value of NLR was 2.78 according to receiver operating characteristic curve. We observed that a high level of baseline NLR (NLR > 2.78) was a poor prognostic factor for overall survival (multivariable hazard ratio [HR] = 2.648, P < 0.001). Increased NLR (ΔNLR > 0) after 2 cycles of chemotherapy was associated with higher risk compared to ΔNLR ≤ 0 (multivariable HR = 1.894, P = 0.007). Combining both NLR and ΔNLR factors, multivariate analysis showed a significant higher risk (HR = 5.817, P < 0.001) for patients with high baseline NLR and increased NLR after 2 cycles of chemotherapy compared to patients with low baseline NLR and ΔNLR ≤ 0. In conclusion, both baseline NLR and ΔNLR are independent prognostic predictors for patients with advanced pancreatic cancer underwent chemotherapy.